Application of Quizzes “BelajarKuy” for Junior High School Based on Android - Nasien, Dewi; Adiya, M. Hasmil; Sirait, Andrio Pratama; Ihsan, M. Nurul; Wicaksono, Mahfuzan Hadi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
In today’s social life, many children to students use gadgets in their daily life. Their gadgets are used mostly android. Android is utilized for all activities namely, games, social media, and others. Besides, the gadget also can be used for education such as quizzes. In this paper, BelajarKuy is proposed for education, especially for junior high school. BelajarKuy is a quiz application based on Android and it uses Java programming language. BelajarKuy contains some questions that are useful for sharpening the brains for students and teachers. Besides, BelajarKuy contains several quizzes which are Mathematics, Bahasa Indonesia, English, Science, Religion, Civic Education, and Social Education. Each quiz has twenty questions and there are four answer choices namely, A, B, C and D. However, it has a solution to the question. At the end of this quiz, students can see scores for all right and wrong questions. This is very helpful in preparing them before an exam that will be given by teachers.